Clinical pearls for the monitoring and treatment of antipsychotic induced metabolic syndrome - Beth M. DeJongh, PharmD, BCPP, BCPS (American Association of Psychiatric Pharmacists, 2021)
Antipsychotic medications increase the risk of metabolic syndrome, which then increases the risk of atherosclerotic cardiovascular disease and premature death. Routinely monitoring for signs of metabolic syndrome in patients taking antipsychotics allows for early detection and intervention. Psychiatric pharmacists can improve patient care through metabolic syndrome monitoring and recommendation of appropriate interventions. Monitoring for the metabolic adverse effects of antipsychotics, management of weight gain, and management of lipids and blood pressure are explored through 2 patient cases.